Conditionally Optimal Algorithms for Generalized Büchi Games - Chatterjee, Krishnendu; Dvořák, Wolfgang; Henzinger, Monika; Loitzenbauer, Veronika (arXiv.org, 2016)
Games on graphs provide the appropriate framework to study several central problems in computer science, such as the verification and synthesis of reactive systems. One of the most basic objectives for games on graphs is the liveness (or B\"uchi) objective that given a target set of vertices requires that some vertex in the target set is visited infinitely often. We study generalized B\"uchi objectives (i.e., conjunction of liveness objectives), and implications between two generalized B\"uchi objectives (known as GR(1) objectives), that arise in numerous applications in computer-aided verification. We present improved algorithms and conditional super-linear lower bounds based on widely believed assumptions about the complexity of (A1) combinatorial Boolean matrix multiplication and (A2) CNF-SAT. We consider graph games with \(n\) vertices, \(m\) edges, and generalized B\"uchi objectives with \(k\) conjunctions. First, we present an algorithm with running time \(O(k · n^2)\), improving the previously known \(O(k · n · m)\) and \(O(k^2 · n^2)\) worst-case bounds. Our algorithm is optimal for dense graphs under (A1). Second, we show that the basic algorithm for the problem is optimal for sparse graphs when the target sets have constant size under (A2). Finally, we consider GR(1) objectives, with \(k_1\) conjunctions in the antecedent and \(k_2\) conjunctions in the consequent, and present an \(O(k_1 · k_2 · n^{2.5})\)-time algorithm, improving the previously known \(O(k_1 · k_2 · n · m)\)-time algorithm for \(m > n^{1.5}\).